2016
DOI: 10.3390/bios6030040
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Intact Viruses Using Aptamers

Abstract: Viral diagnosis and surveillance are necessary steps in containing the spread of viral diseases, and they help in the deployment of appropriate therapeutic interventions. In the past, the commonly employed viral detection methods were either cell-culture or molecule-level assays. Most of these assays are laborious and expensive, require special facilities, and provide a slow diagnosis. To circumvent these limitations, biosensor-based approaches are becoming attractive, especially after the successful commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…In many cases, aptamers possessing neutralizing activity have been regarded as important components of antiviral strategies 27 , 29 , 32 and have been clinically used to treat viral infection 14 , 33 . In this study aptamer IBRV-A4 had a neutralization titre of 1:55 and was shown to efficiently inhibit multiplication of BoHV-1 in MDBK cells as shown by plaque reduction assay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, aptamers possessing neutralizing activity have been regarded as important components of antiviral strategies 27 , 29 , 32 and have been clinically used to treat viral infection 14 , 33 . In this study aptamer IBRV-A4 had a neutralization titre of 1:55 and was shown to efficiently inhibit multiplication of BoHV-1 in MDBK cells as shown by plaque reduction assay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers are also much more stable than antibodies making them suitable in applications requiring harsh conditions, (e.g., high temperature or extreme pH) [143]. General review articles about aptamer-based sensors [144] and aptamer-based sensors for viruses are available in literature [145][146][147].…”
Section: Aptamersmentioning
confidence: 99%
“…Their lower molecular weight enhances the stability to sustain repetitious denaturation and renaturation. Aptasensor, due to its advantages, is increasingly explored, particularly in intact virus detection using SPR and other platforms 127 .…”
Section: Other Advanced Technologies In Poc Of Foodborne Virusesmentioning
confidence: 99%